Pengaruh Asset Tidak Berwujud terhadap Nilai Perusahaan - Setijawan, Imam (STIE Widya Manggala, 2011)
Accounting for intangibles assets became a subject of accounting debate in many countries. This research intend to study the influence of intangibles assets, including their amortization expenses, to firm value. The results shown that goodwill has no effect on firm value, on contrary others intangibles assets and amortization expenses have significant effetcs on firm value. This results indicated that others intangibles assets, like intelectual capital, have an important value in the future and became attention’s focus for investors.